2003
DOI: 10.1177/1052562903027003006
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Teams to be Teams: An Exercise Using the Myers-Briggs® Type Indicator and the Five-Factor Personality Traits —

Abstract: This article reports results of a student-team intervention that used team members' personality assessments on the Myers-Briggs Type Indicator and the Five-Factor Model to enhance the team development process and engender an appreciation of the effect of different personalities on team functioning and performance. The majority of participants reported that knowledge of team members' personality types was helpful in understanding team member behavior and was used in managing team dynamics. Those teams that used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…As has been argued in the literature review, this type of assessment cannot be rushed. The study of Clinebell et al, (2003) indicates that students need sufficient time to become familiar with each other, and to set up proper group processes. A group project crammed into a six or even a ten-week cycle is unlikely to be a valuable learning tool.…”
Section: Discussionmentioning
confidence: 99%
“…As has been argued in the literature review, this type of assessment cannot be rushed. The study of Clinebell et al, (2003) indicates that students need sufficient time to become familiar with each other, and to set up proper group processes. A group project crammed into a six or even a ten-week cycle is unlikely to be a valuable learning tool.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of team member's personality types helps to understand team member behavior, managing the dynamics of the team and to know how team members interact well in a group setting to accomplish the task [35]. Previous studies found correlations between individual personality and performance on a team [2] [11].…”
Section: Team Formation Personality and Team Performancementioning
confidence: 99%
“…In another study, Cooper and Miller (1991) were able to gain insight into how well or misaligned student learning style preferences are to faculty teaching styles. Another positive outcome of the personality profile application in educational settings is in raising students' awareness of personality and learning preferences, and thereby fostering more effective learning in general, and especially in the context of group or teamwork (Amato & Amato, 2005;Clinebell & Stecher, 2003;Goby & Lewis, 2000;Page & Donelan, 2003;Rideout & Richardson, 1989).…”
Section: How Students Learn: Personal Attributesmentioning
confidence: 99%